2018
DOI: 10.1038/s41390-018-0069-x
|View full text |Cite
|
Sign up to set email alerts
|

The lifelong impact of fetal growth restriction on cardiac development

Abstract: Background Maternal nutrient restriction (MNR) is a widespread cause of fetal growth restriction (FGR), an independent predictor of heart disease and cardiovascular mortality. Our objective was to examine the developmental and long-term impact of MNR-induced FGR on cardiac structure in a model that closely mimics human development. Methods A reduction in total caloric intake spanning pre-gestation through to lactation in guinea pig sows was used to induce FGR. Proliferation, differentiation, and apoptosis of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 43 publications
0
21
0
1
Order By: Relevance
“…These studies show that the fetal heart is remodeled in a manner similar to that seen in dilated cardiomyopathy. Cardiomyocyte development is adversely affected and programmed cell death is increased in growth restricted fetal guinea pigs and sheep, with a persistence of the mononucleated, primitive cell type (70, 71). Permanent alterations in heart morphology are detected into adulthood, as evidenced by persistence in the deficits in cardiomyocyte number and cardiac hypertrophy (70).…”
Section: Specific Neonatal Morbidities (Table 1)mentioning
confidence: 99%
“…These studies show that the fetal heart is remodeled in a manner similar to that seen in dilated cardiomyopathy. Cardiomyocyte development is adversely affected and programmed cell death is increased in growth restricted fetal guinea pigs and sheep, with a persistence of the mononucleated, primitive cell type (70, 71). Permanent alterations in heart morphology are detected into adulthood, as evidenced by persistence in the deficits in cardiomyocyte number and cardiac hypertrophy (70).…”
Section: Specific Neonatal Morbidities (Table 1)mentioning
confidence: 99%
“…Similar observations have been made in precocious developers, like guinea pigs, that closely mimic human gestation. Fetal hearts isolated from growth-restricted guinea pigs are proportionately small compared to controls, but exhibit a significant reduction in cardiomyocyte number without alteration in the number of mononuclear cells [3]. However, during the final maturation phases of cardiac development, growth-restricted guinea pig hearts consistently demonstrate a high number of proliferative cardiomyocytes in the fetal and early post-natal phase relative to control hearts, but the total number of cardiomyocytes in growth restricted hearts continues to lag behind controls suggesting that cardiomyocyte expansion is impaired.…”
Section: Discussionmentioning
confidence: 97%
“…Early development and maturation of the cardiovascular system may contribute to the increased susceptibility of the heart and blood vessels to poor fetal growth. Animal models have demonstrated that cardiac mass is largely determined at birth, and the number of proliferating cardiomyocytes quickly diminishes over the first months postnatally [3,4]. This limited capacity to regenerate new cardiomyocytes forces the heart to enlarge through cardiomyocyte hypertrophy rather than hyperplasia in response to physiologic increases in systemic vascular resistance as infants grow.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations